2019
DOI: 10.3390/jcm8030372
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Impact of Acute Kidney Injury after Liver Transplantation: A Meta-Analysis

Abstract: Background: The study’s aim was to summarize the incidence and impacts of post-liver transplant (LTx) acute kidney injury (AKI) on outcomes after LTx. Methods: A literature search was performed using the MEDLINE, EMBASE and Cochrane Databases from inception until December 2018 to identify studies assessing the incidence of AKI (using a standard AKI definition) in adult patients undergoing LTx. Effect estimates from the individual studies were derived and consolidated utilizing random-effect, the generic invers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
92
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 101 publications
(100 citation statements)
references
References 101 publications
7
92
1
Order By: Relevance
“…Those needs that are classified as unmet require provision of some ample spaces for the purpose of imagination in relation to leveraging the strength associated with big data, as well as relevant artificial intelligence (AI) to improve the overall status of patients with kidney diseases [25]. In this article, we discuss the big data concepts in nephrology, describe the potential use of AI in nephrology and transplantation, and also encourage researchers and clinicians to submit their invaluable research, including original clinical research studies [26][27][28][29][30], database studies from registries [31][32][33], meta-analyses [34][35][36][37][38][39][40][41][42][43][44], and artificial intelligence research [25,[45][46][47][48] in nephrology and transplantation. Table 1 demonstrates known and commonly used databases that have provided big data in nephrology and transplantation [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Those needs that are classified as unmet require provision of some ample spaces for the purpose of imagination in relation to leveraging the strength associated with big data, as well as relevant artificial intelligence (AI) to improve the overall status of patients with kidney diseases [25]. In this article, we discuss the big data concepts in nephrology, describe the potential use of AI in nephrology and transplantation, and also encourage researchers and clinicians to submit their invaluable research, including original clinical research studies [26][27][28][29][30], database studies from registries [31][32][33], meta-analyses [34][35][36][37][38][39][40][41][42][43][44], and artificial intelligence research [25,[45][46][47][48] in nephrology and transplantation. Table 1 demonstrates known and commonly used databases that have provided big data in nephrology and transplantation [49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…In patients with chronic kidney disease (CKD), a high burden of cardiovascular diseases (CVD) is common, and an inverse correlation of renal function with the prevalence of coronary artery disease, congestive heart failure, and cerebrovascular disease is observed [1,50]. Moreover, the incidence of acute kidney injury has been steadily increasing in recent years, leading to higher healthcare costs and mortality and contributing to increasing prevalence rates of CKD [51,52]. With an increasing prevalence of CKD from variable causes, the number of patients with end-stage renal disease is on the rise [1,53].…”
Section: Discussionmentioning
confidence: 99%
“…The global burden of AKI is around 13.3 million cases per year with hospitalizations for AKI rising over time. A published meta-analysis showed that in the United States alone, AKI is associated with 1 hospitalization every 7.5 minutes [8]. A single-center study reported that the in-hospital mortality rate and 6-month survival rate of patients treated with ECMO who had concomitant AKI were worse than those of patients who did not develop AKI [6].…”
Section: Introductionmentioning
confidence: 99%